Green Strategy of Shell Brick for Sustainable Architecture - Ardiansyah Ardiansyah; Muhammad Rijal (Universitas Muhammadiyah Surakarta, 2026)
The construction industry contributes significantly to global carbon emissions and environmental degradation, creating increasing demand for sustainable building materials. This research aims to formulate a green strategy for enhancing the value of shell brick as an environmentally friendly building material within the perspective of sustainable architecture and circular economy principles. The study uses a qualitative case study approach through SWOT analysis integrated with Olson’s Green Strategy framework. Primary data were collected through observations, interviews, and documentation studies involving shell brick industries in Dumai City, Indonesia. The results identify seven strategic dimensions requiring development, namely raw material management, production techniques, processing technology, distribution systems, marketing strategies, institutional development, and architectural applications. The findings indicate that shell brick has strong potential as a sustainable architectural material due to its utilization of palm oil industrial waste through reuse, reduce, and recycle principles. The study also demonstrates that shell brick supports green building concepts through reduced embodied carbon potential, local resource utilization, and environmentally responsive architectural applications. This research contributes to the development of sustainable construction materials and green architecture practices in tropical regions.